Year of Francysk Skaryna in Lithuania, Poland and the Czech Republic - Parshankou, Aliaksandr (Slavistica Vilnensis, 2023)
The year 2022 was announced in Lithuania by the decision of the Seimas of the Republic of Lithuania in the years of Francysk Skaryna. It was marked by the publication of monographs dedicated to the outstanding cultural figure, a number of conferences where controversial issues of the life and work of Francysk Skaryna were discussed, a summer school - a joint event of the Czech Republic and Lithuania, exhibitions, film projects, and publications in the press. The events of 2022 in Lithuania, Poland, the Czech Republic, in which scientists, librarians, creative teams took part, and the continuation of scoriniana in 2023, indicate that the legacy of Francysk Skorina does not lose its relevance.